Post-COVID-19 Syndrome: The Persistent Symptoms at the Post-viral Stage of the Disease. A Systematic Review of the Current Data - Salamanna, Francesca; Veronesi, Francesca; Martini, Lucia; Landini, Maria Paola; Fini, Milena (Frontiers in Medicine, 2021)
Whilst the entire world is battling the second wave of COVID-19, a substantial proportion of patients who have suffered from the condition in the past months are reporting symptoms that last for months after recovery, i.e. long-term COVID-19 symptoms. We aimed to assess current evidence on the long-term symptoms in COVID-19 patients. We did a systematic review on PubMed, Web of Science, EMBASE and Google Scholar from database inception to February 15, 2021, for studies on long-term COVID-19 symptoms. We included all type of papers that reported at least one long-term COVID-19 symptom. We screened studies using a standardized data collection form and pooled data from published studies. Cohort cross-sectional, case-report, cases-series, case-control studies, and review were graded using specific quality assessment tools. Of 11,361 publications found following our initial search we assessed 218 full-text articles, of which 145 met all selection criteria. We found that the 20.70% of reports on long-term COVID-19 symptoms were on abnormal lung functions, the 24.13% on neurologic complaints and olfactory dysfunctions and the 55.17% on specific widespread symptoms, mainly chronic fatigue, and pain. Although the relatively high heterogeneity of the reviewed studies, our findings highlighted that a noteworthy proportion of patients who have suffered from SARS-CoV-2 infection present a ‘post-COVID syndrome’. The multifaceted understanding of all aspects of the COVID-19 pandemic, including these long-term symptoms, will allow us to respond to all the global health challenges, thus paving the way to a stronger public health.